Analisis Kesulitan Mahasiswa Prodi Teknik Industri dalam Memahami Konsep Kinematika - Budhi, Widodo; Amalia, Ayu Fitri; Purnama, Aditya Yoga (Navigation Physics : Journal of Physics Education, 2024)
This study aims to identify factors of student difficulties and analyze student difficulties in understanding the concept of kinematics in working on odd semester midterm exam questions in the 2023/2024 academic year Basic Physics 1 subject kinematics. This research was conducted at the Industrial Engineering Study Program, Faculty of Engineering, Sarjanawiyata Tamansiswa University in the odd semester of the 2023/2024 academic year. This research is a descriptive research. The research population was all Industrial Engineering students who took Basic Physics 1 course totaling 78 students. This research is a descriptive type of research. The research population is all Industrial Engineering students who take Basic Physics 1 courses totaling 78 students. The results showed that students' difficulties in understanding the concept of kinematics were categorized into 3 (three) factors, namely concepts (84%), procedures (47%), and mathematical calculations (67%). Students' ability to understand the concept of kinematics still tends to be low, this is indicated by the average score obtained by students only reaching 28.55 with a standard deviation of 10.53.